2009
DOI: 10.3382/ps.2008-00238
|View full text |Cite
|
Sign up to set email alerts
|

Higher incorporation of heterologous chicken immunoglobulin Y compared with homologous quail immunoglobulin Y into egg yolks of Japanese quail (Coturnix japonica)

Abstract: In avian species, blood IgY is selectively incorporated into the yolks of maturing oocytes, although the precise mechanism is poorly understood. Our previous study showed that 22% of i.v.-injected heterologous chicken IgY (cIgY) was incorporated into egg yolks of Japanese quail (Coturnix japonica). However, it is not known whether homologous quail IgY (qIgY) can be more efficiently incorporated into quail egg yolks than cIgY. Therefore, we compared the uptakes of qIgY and cIgY i.v. administered into quail egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…We have also compared the uptake of quail IgY and chicken IgY into egg yolks of quail. Unexpectedly, the uptake of quail IgY was only one-third of the uptake of chicken IgY, implying that heterologous chicken IgY is far preferable as a ligand for transport into egg yolks of quail compared to homologous quail IgY (Bae et al, 2009). The examination of tissue distribution and blood clearances showed that higher deposition of quail IgY in various body tissues might lead to lower uptake of quail IgY into ovarian follicles.…”
Section: Three Classes Of Avian Igs and Heterologous Igsmentioning
confidence: 97%
“…We have also compared the uptake of quail IgY and chicken IgY into egg yolks of quail. Unexpectedly, the uptake of quail IgY was only one-third of the uptake of chicken IgY, implying that heterologous chicken IgY is far preferable as a ligand for transport into egg yolks of quail compared to homologous quail IgY (Bae et al, 2009). The examination of tissue distribution and blood clearances showed that higher deposition of quail IgY in various body tissues might lead to lower uptake of quail IgY into ovarian follicles.…”
Section: Three Classes Of Avian Igs and Heterologous Igsmentioning
confidence: 97%
“…In other related studies, two bands of heavy and light chains of both chicken and quail IgYs at the same molecular weights on SDS‐PAGE analysis under reducing conditions were obtained (Bae et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…However, the transfer of antibodies also appear to be directly correlated to the increase in size of yolk as an egg is formed [10] so investment may be tied to allocation of other constituents laid down in the last few days of egg formation (though we foud no evidence that a female’s average egg size is related to her general level of transfer). There may also be variation in transfer levels based on variation in antibodies produced; for example, surprisingly, quail have been shown to transfer higher levels of chicken IgY than quail IgY in experimental manipulations [29]. How the molecules of IgY may vary between and within individuals remains unclear and is something seldom considered by immunologists as detection techniques tend to target specific known parts of the molecule making this hard to address (J. Allen pers.com).…”
Section: Discussionmentioning
confidence: 99%
“…For the Paramyxo P201 treated individuals, a Newcastle disease virus-specific ELISA test was performed using FLOCKTYPE® recNDV ELISA kit (Labor Diagnostik Leipzig, Germany). Both kits were manufactured for chicken serum and plasma but quail antibodies are also detected and a number of studies have used anti chicken antibody to detect antibodies in quails [29,35,46]. Previous pilot work had established the appropriate dilutions to ensure antibodies lay within the bounds of the detectable range of the ELISA kits and dilution curves confirmed these lay within the linear part of the test.…”
Section: Methodsmentioning
confidence: 99%